login
The OEIS is supported by the many generous donors to the OEIS Foundation.

 

Logo
Hints
(Greetings from The On-Line Encyclopedia of Integer Sequences!)
A357789 a(n) = coefficient of x^(2*n) in S(x) defined by: C(x) + i*S(x) = Sum_{n=-oo..+oo} i^n * (2*x)^(n^2) * F(x)^n, where F(x) is the g.f. of A357787 such that C(x)^2 + S(x)^2 = 1. 5
8, 32, 128, 0, -9216, -94208, -671744, -3014656, 1245184, 171704320, 1756364800, 8338276352, -26013073408, -946201427968, -10033714692096, -56471303749632, 43465874341888, 4967278927937536, 61805829224923136, 423546310109429760, 713014908152709120, -24149207336980840448 (list; graph; refs; listen; history; text; internal format)
OFFSET
1,1
LINKS
FORMULA
Given g.f. S(x) = Sum_{n>=1} a(n)*x^(2*n) and related functions C(x) and F(x) (g.f. of A357787) satisfy the following.
(1) C(x)^2 + S(x)^2 = 1.
(2) C(x) + i*S(x) = Sum_{n=-oo..+oo} i^n * (2*x)^(n^2) * F(x)^n.
(3) 1/F(x) = F(-x).
(4) C(x) = 1 + Sum_{n>=1} (-1)^n * (2*x)^(4*n^2) * (F(x)^(2*n) + F(-x)^(2*n)).
(5) S(x) = Sum_{n>=0} (-1)^n * (2*x)^((2*n+1)^2) * (F(x)^(2*n+1) - F(-x)^(2*n+1)).
(6) C(x) + i*S(x) = Product_{n>=1} (1 + i*(2*x)^(2*n-1)*F(x)) * (1 - i*(2*x)^(2*n-1)/F(x)) * (1 - (2*x)^(2*n)), due to the Jacobi triple product identity.
EXAMPLE
G.f.: S(x) = 8*x^2 + 32*x^4 + 128*x^6 - 9216*x^10 - 94208*x^12 - 671744*x^14 - 3014656*x^16 + 1245184*x^18 + 171704320*x^20 + 1756364800*x^22 + 8338276352*x^24 - 26013073408*x^26 - 946201427968*x^28 - 10033714692096*x^30 - 56471303749632*x^32 + ...
such that S(x) and C(x) = sqrt(1 - S(x)^2) form the real and imaginary parts of the doubly infinite sum
C(x) + i*S(x) = Sum_{n=-oo..+oo} i^n * (2*x)^(n^2) * F(x)^n
where F(x) is the g.f. of A357787 and normalizes the given theta series so that C(x)^2 + S(x)^2 = 1.
Explicitly,
C(x) = 1 - (2*x)^4*(F(x)^2 + F(-x)^2) + (2*x)^16*(F(x)^4 + F(-x)^4) - (2*x)^36*(F(x)^6 + F(-x)^6) + (2*x)^64*(F(x)^8 + F(-x)^8) + ... + (-1)^n * (2*x)^(4*n^2) * (F(x)^(2*n) + F(-x)^(2*n)) + ...
S(x) = (2*x)*(F(x) - F(-x)) - (2*x)^9*(F(x)^3 - F(-x)^3) + (2*x)^25*(F(x)^5 - F(-x)^5) - (2*x)^49*(F(x)^7 - F(-x)^7) + ... + (-1)^n * (2*x)^((2*n+1)^2) * (F(x)^(2*n+1) - F(-x)^(2*n+1)) + ...
where
F(x) = 1 + 2*x + 2*x^2 + 8*x^3 + 14*x^4 + 32*x^5 + 68*x^6 + 22*x^8 - 768*x^9 - 2020*x^10 - 9216*x^11 - 23156*x^12 - 45056*x^13 - 115320*x^14 + 32768*x^15 + ... + A357787(n) * x^n + ...
C(x) = 1 - 32*x^4 - 256*x^6 - 2048*x^8 - 12288*x^10 - 32768*x^12 + 131072*x^14 + 3276800*x^16 + 28311552*x^18 + 125829120*x^20 - 285212672*x^22 - 11274289152*x^24 + ... + A357788(n)*x^(2*n) + ...
PROG
(PARI) {a(n) = my(F=[1, 2], THETA=1); for(i=1, 2*n, F = concat(F, 0); m=sqrtint(#F+9);
THETA = sum(n=-m, m, I^n * (2*x)^(n^2) * truncate(Ser(F))^n + x*O(x^(#F+2)));
F[#F] = -polcoeff( (real(THETA)^2 + imag(THETA)^2)/64, #F+2)); polcoeff(imag(THETA), 2*n)}
for(n=1, 25, print1(a(n), ", "))
CROSSREFS
Sequence in context: A234272 A269077 A183915 * A363333 A358253 A358252
KEYWORD
sign
AUTHOR
Paul D. Hanna, Dec 05 2022
STATUS
approved

Lookup | Welcome | Wiki | Register | Music | Plot 2 | Demos | Index | Browse | More | WebCam
Contribute new seq. or comment | Format | Style Sheet | Transforms | Superseeker | Recents
The OEIS Community | Maintained by The OEIS Foundation Inc.

License Agreements, Terms of Use, Privacy Policy. .

Last modified April 16 17:08 EDT 2024. Contains 371749 sequences. (Running on oeis4.)